2018
DOI: 10.18632/oncotarget.26259
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive regulation of thiamine pyrophosphokinase-1 facilitates malignant growth during supplemental thiamine conditions

Abstract: Supplemental levels of vitamin B1 (thiamine) have been implicated in tumor progression. Tumor cells adaptively up-regulate thiamine transport during hypoxic stress. Upon uptake, thiamine pyrophosphokinase-1 (TPK1) facilitates the rapid phosphorylation of thiamine into thiamine pyrophosphate (TPP). However, the regulation of TPK1 during hypoxic stress is undefined. Understanding how thiamine homeostasis changes during hypoxia will provide critical insight into the malignant advantage supplemental thiamine may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The major intracellular derivative of thiamine, ThDP, has been added instead of thiamine in view of ThDP involvement in regulation of p53 transcriptional activity ( McLure et al, 2004 ). Given published evidence on transport of ThDP by cellular membrane transporters SLC19A1 ( Zhao et al, 2001 ; Zhao and Goldman, 2013 ) and SLC44A4 ( Nabokina et al, 2014 ), this experimental design may overcome complex regulation of ThDP synthesis in cancer cells ( Jonus et al, 2018 ), being more straightforward to extend the interval of intracellular ThDP content. Expression of SLC19A1 is documented in A549 cells ( Kawami et al, 2015 ), as is the expression of choline transporters-like CTL/SLC44 proteins ( Inazu, 2014 ) sharing the same family with the ThDP-transporting SLC44A4.…”
Section: Resultsmentioning
confidence: 99%
“…The major intracellular derivative of thiamine, ThDP, has been added instead of thiamine in view of ThDP involvement in regulation of p53 transcriptional activity ( McLure et al, 2004 ). Given published evidence on transport of ThDP by cellular membrane transporters SLC19A1 ( Zhao et al, 2001 ; Zhao and Goldman, 2013 ) and SLC44A4 ( Nabokina et al, 2014 ), this experimental design may overcome complex regulation of ThDP synthesis in cancer cells ( Jonus et al, 2018 ), being more straightforward to extend the interval of intracellular ThDP content. Expression of SLC19A1 is documented in A549 cells ( Kawami et al, 2015 ), as is the expression of choline transporters-like CTL/SLC44 proteins ( Inazu, 2014 ) sharing the same family with the ThDP-transporting SLC44A4.…”
Section: Resultsmentioning
confidence: 99%
“…As already suggested for BFT, the coenzyme ThDP does not seem to be involved: we showed that in the presence of pyrithiamine, no net ThDP synthesis occurred during incubation with DBT, but its protective effects were maintained both in Neuro2a and BV2 cells ( Figure 13 ). It was recently suggested that ThDP could have an antioxidant effect that is independent of its coenzyme role [ 55 ]. DBT was no more efficient in raising intracellular ThDP concentrations than thiamine, SuBT, or BFT in Neuro2a ( Supplemental Figure S2 ) and BV2 cells ( Supplemental Figure S12 ), though it was pharmacologically more active.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the upregulation of TPK1, intracellular TPP was decreased. SiRNA knockdown of TPK1 reduced tumor cell proliferation, suggesting that increased TPP supports increased tumor growth [20]. A study motivated by the observation of poor thiamine bioavailability in tumors developed thiamine mimetics to improve delivery to cells.…”
Section: Thiamine B1mentioning
confidence: 99%